Factores que inciden en el éxito en ventas a través del uso de los medios sociales en las empresas turísticas y hoteleras de primera categoría de la ciudad de Loja - cantón Loja - provincia Loja - Cedeño Zambrano, María Isabel (2014)
The present work have the purpose to improve the success of turism companies and hotel present in the city of Loja. The investigation make a refence at the theoretical fundamentation in a relation with the identification of intangible resources and the capacity of the staff of the company linked to social media, allowing gain a competitive advantage in sales compared to other hotels and tourism businesses, it also, conceptualized the different alternatives for social media, habitually used to have a presence on the web 2.0 and achieve commercial success. Then, it describes the results of field research where mention the opinions of employers and / or managers of the tourist establishments and hotels and also the most important causes that motivate purchase intention with customers to make use of the services provided by hotels and tourism businesses through social media. Finally as a contribution, is included a section that consists of a basic instructive for companies to increase their sales through the correct use of social media